The Influence of Career Development on Employee Performance with Self Efficacy as a Mediating Variable - Kakiay, Justicia Claydie; Risambessy, Agusthina; Rehatta, Pieter Novry Ruddy Rehatta (Public Policy, 2025)
This study aims to empirically test the influence of career development on employee performance with self-efficacy as a mediating variable at the Regional Tax and Retribution Management Agency (BPPRD) of Ambon City. The research used a quantitative method with 38 civil servants as the sample, selected through simple random sampling. Data were collected via questionnaires and analyzed using Smart PLS 3. The results show that career development has a significant and positive effect on employee performance. Additionally, self-efficacy significantly mediates the relationship between career development and employee performance. These findings suggest that employee development programs should focus not only on technical skills but also on building self-confidence to enhance performance outcomes. Keywords : career development, employee performance, self efficacy